Establishment of an Integrated Development Post (POSBINDU) for Non-Communicable Diseases (Ncds) in the Community of Karunrung Subdistrict, Makassar City - Muhasidah, Muhasidah; Iwan, Iwan; Ahmad, Abd Kadir; Hartati, Hartati; Baharuddin, Baharuddin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
A situational analysis based on research conducted by Muhasidah et al. (2023) on 128 respondents showed that more than 50% of them suffered from Non-Communicable Diseases (NCDs). Among these, 67 respondents had hypertension, with 32 not taking hypertension medication regularly and 8 not taking medication at all. The irregular intake of antihypertensive drugs can lead to complications such as stroke, heart abnormalities, and kidney disease. Makassar City recorded a total of 5,632 hypertension cases (8.9%), the highest prevalence in South Sulawesi. Karunrung Subdistrict, under the working area of the Kassi-kassi Community Health Center, had the highest cases of hypertension in Makassar City. The implementing partner's priority problem was the high rate of hypertension in the area, along with the absence of an Integrated Development Post (Posbindu) for NCDs. The target partner community also lacked awareness about the importance of consistently taking antihypertensive medication to prevent complications such as stroke, heart abnormalities, and kidney disorders. The objectives of this activity were to establish an Integrated Development Post (Posbindu) for NCDs, increase the target partner's knowledge and ability to conduct Posbindu activities, educate families about the prevention and management of NCDs, and reduce the incidence of NCDs by 20–30% within one year. The proposed solutions included training target groups, providing guidebooks, implementing the five-table Posbindu NCD activities, encouraging the community to participate in weekly physical exercise for NCDs, and distributing guidebooks on NCDs and Posbindu activities prepared by the community service team. The partner's contribution included providing a permanent facility that could be used as the Posbindu NCD. The expected outcomes of this activity were the establishment of a Posbindu NCD in RW 08, increased knowledge among target partners from 50% to 80%, the initiation of weekly NCD exercise sessions, and a reduction in NCD cases by 20–30% during the year. The community service results showed significant improvement in knowledge, understanding, and attitudes among cadres and individuals with NCDs. A Posbindu was successfully established with the help of the community service team and implementing partners, including the Kassi-kassi Health Center. The sustainability of the Posbindu activities will be handed over to the implementing partners, namely the Kassi-kassi Health Center and the local community groups (Majelis Taklim).